FDI, Political Risk, and Government Policy - Damiana Simanjuntak (EKO-REGIONAL, 2018)
Investment will create a multiplier effect for the economy, especially investments from abroad which may also encourage the technology spillover and innovation process. Political risk and government investment policy are two factors considered by investors in investing. This research aimed to determine the effect of these two factors on foreign direct investment (FDI) in Indonesia. This research used data of FDI in Indonesia in 2010-2017, during which there were three changes in foreign direct investment policies in Indonesia and one political year. Using panel data analysis, this research found that government policy in revising the negative investment list had no significant effect on FDI flows in Indonesia. It can be seen that the sector effect experiencing a tightening of foreign asset ownership limitation on FDI was greater than the sector effect experiencing loosening of asset ownership limitation by foreign parties. In addition, this research found that political risk had no significant effect on FDI in Indonesia.Keywords: FDI, Politics, Policy.